Other people's fun - Lane, Harriet (Little, Brown and Company, 2025)
"Ruth is alone, unnoticed, and at a loss: her marriage has ended, her daughter is leaving home, and her job is leading nowhere. But luckily Sookie is back in her life-vivid, self-assured Sookie, who never spared the time for Ruth when they were teenagers, but who now seems to want to be friends. But as Ruth is caught up in Sookie's life, she sees that everything is not as Instagrammable as Sookie would have you believe. As the truth about Sookie becomes clearer, so too does the choice Ruth will have to make."--